2007
DOI: 10.1002/jgm.1099
|View full text |Cite
|
Sign up to set email alerts
|

Transient non‐viral cutaneous gene delivery in burn wounds

Abstract: Lipofectamine 2000 and DOTAP/Chol lipoplex showed significantly enhanced gene transfer, whereas no transfection was detectable for naked DNA in vitro. In contrast to the in vitro study, naked DNA was the only agent with which gene delivery was successful in experimental burn wounds. These findings highlight the limited predictability of in vitro analysis for gene delivery as a therapeutic approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…However, in vivo studies of a mouse intraperitoneal fat model showed that only the use of naked, plasmid DNA–containing scaffolds yielded successful long-term transgene delivery, which was determined by higher expression levels of both luciferase and green fluorescent protein. Several other groups (138141) have also reported this contradiction between in vitro and in vivo results, which may be due to the interactions among carriers, host tissue, and immunity that cannot be adequately replicated in an in vitro setting. In addition to the delivery of nonviral vectors, POC has been investigated for use as a substrate to deliver genes via a lentivirus.…”
Section: Applications In Regenerative Engineeringmentioning
confidence: 97%
“…However, in vivo studies of a mouse intraperitoneal fat model showed that only the use of naked, plasmid DNA–containing scaffolds yielded successful long-term transgene delivery, which was determined by higher expression levels of both luciferase and green fluorescent protein. Several other groups (138141) have also reported this contradiction between in vitro and in vivo results, which may be due to the interactions among carriers, host tissue, and immunity that cannot be adequately replicated in an in vitro setting. In addition to the delivery of nonviral vectors, POC has been investigated for use as a substrate to deliver genes via a lentivirus.…”
Section: Applications In Regenerative Engineeringmentioning
confidence: 97%
“…Studies investigating skin disorders in humans are limited owing to ethical concerns, leading to dependence on in vitro and experimental animal models to investigate novel therapies and biologic and pathophysiologic pathways [3]. Many models have been developed [7], but in vitro and in vivo models may show poor consistency with clinical situations [27]. …”
Section: Introductionmentioning
confidence: 99%
“…Interspecies differences in anatomy and physiology, differences in cause and course between natural human disease and artificially induced nonhuman pathology, and stress experienced by animals in laboratories invariably alter research results. Few in vitro or nonmammalian surrogate experiments accurately or adequately duplicate, or recapitulate, the full physiology of the human model for wound healing purposes [27]. Many research efforts seek new innovative approaches to in vitro modeling of in vivo complexity without clear progress or improved relevance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,16 However, very few in vitro models can completely reproduce the physiology of human skin for wound repair studies. 17 Lack of multidimensional growth makes the mono-layer keratinocyte culture a less robust tool for wound healing investigation. Despite the fact that both keratinocyte-fibroblast co-culture and organotypic culture have the characters of three-dimensional cell culture, their fidelity to in vivo is still limited.…”
mentioning
confidence: 99%